Walter Benjamin and Erich Kästner. The Story of Two Moralists - Ekaterina B. Kriukova; Oxana A. Koval (Studia Litterarum)
The article focuses on the life and work of two German intellectuals, the philosopher Walter Benjamin and the writer Erich Kästner, who played a prominent role in the cultural life of Berlin in the 1920s. The idea of a comparative analysis of these two figures was prompted by Kästner’s novel Fabian. The Story of a Moralist. This novel is of interest due to its high literary quality, on the one hand, and the authenticity of the representation of the Weimar Republic on the other, which allows us to consider Kästner’s book as a document of the era. According to German researchers, the main characters of the novel have real-life prototypes, namely the author himself and the famous philosopher Walter Benjamin. This idea is developed and reinforced in the article. Therefore, the article parallels draws parallels between biographical facts and plot devices while reconstructing the context of the novel’s creation and highlighting events that occurred after its appearance. Based on this analysis, we argue that the key characters represent two ways of ethical existence in a society where moral values are negated by cynical reason. Thus, involving Benjamin’s philosophical theories, as well as Kästner’s war diaries, we outline the background of the debate on moral priorities that takes place in the pages of the novel.